Corrigendum to ‘flexible circuits in the d $d$‐dimensional rigidity matroid’ - Georg, Grasegger; Hakan, Guler; Bill, Jackson; Anthony, Nixon (Wiley, 2022)
zbMATH Open Web Interface contents unavailable due to conflicting licenses.
Keywords: Rigidity and flexibility of structures (aspects of discrete geometry); Combinatorial aspects of matroids and geometric lattices; Planar graphs; geometric and topological aspects of graph theory